Stereotactic focal radiotherapy as an alternative treatment for low-risk prostate cancer: Results of a single-arm monocenter Phase-II trial - Nguyen, Paul V.; Donneaux, Bertrand; Louis, Céline; Bodgal, Zsuzsa; Philippi, Sven; Biver, Sylvie; Frederick, Bérangère; Harzé, Ludovic; Lasar, Yves; Vogin, Guillaume; Nickers, Philippe (Frontiers in Oncology, 2023)
Introduction Since radical treatments in low risk prostate cancer do not improve overall survival in comparison to active surveillance, preserving quality of life (QOL) remains the key objective. Active surveillance of indolent prostate cancer avoids curative treatment side-effects but necessitates repeated biopsies. Focal stereotactic body radiation therapy (focal SBRT) may be an alternative. This non-randomized Phase-II trial examined the feasibility and safety of focal SBRT for low and favorable intermediate-risk prostate cancer. Methods Patients were recruited in 2016–2019 if they had: localized CAPRA ≤ 3 prostate adenocarcinoma; an isolated PIRADS≥4 macroscopic tumor on MRI; WHO Performance Status 0-1; and no major urinary symptoms. 36.25 Gy (80% isodose prescription) were delivered in 5 fractions every other day. Primary outcome was delay between focal SBRT and salvage-treatment initiation. Secondary outcomes were: acute/late genitourinary/rectal toxicity; biological, clinical and MRI local control; and change in QOL measures. Results Over a median follow-up of 36 months, salvage prostatectomy in the 24 eligible patients was never required. Three-year biochemical progression-free survival was 96%. The single biochemical recurrence was a small (2-mm) Gleason 6 (3 + 3) lesion in the non-irradiated lobe. All 19 patients with ≥1 post-treatment MRI evaluations demonstrated complete radiological response. Acute/late grade ≥3 toxicities did not occur: all acute toxicities were grade-1 genitourinary (38% patients), grade-2 genitourinary (8%), or grade-1 rectal (13%) toxicities. There was one (4%) late grade-1 genitourinary toxicity. QOL was unchanged at last follow-up, as shown by IPSS (2.86 to 3.29, p>0.05), U-QOL (0.71 to 0.67, p>0.05), and IIEF5 (the 14 initially potent patients maintained potency (IIEF5 > 16)). Conclusion Focal SBRT is feasible, well-tolerated, and preserves QOL. This innovative robotized approach challenges active surveillance.